Sequence stratigraphy in British geology - Hesselbo, S; Parkinson, D (Geological Society, London; Special Publication, 103, 1996)
This volume contains 13 papers (abstracted separately) covering surface and subsurface rocks from a wide range of stratigraphic ages and sedimentary environments. The book focuses on diverse aspects of sequence stratigraphy that tend to cut across divisions based on depositional environments or age alone. There are two main themes that run through most of the papers: 1. Because biostratigraphical control is often so good in much of Britain, precise correlations are possible within and between basins. Therefore, many of the British outcrop sections serve as standards that can be compared to other areas around the world. 2. The papers illustrate the way in which sequence stratigraphical ideas can cast new light on problematic facies. In return, problematic facies can offer critical insights into the sequence stratigraphical model. -from Editors